Molecular treatment trajectories within psoriatic T lymphocytes: a mini review - Kuczyńska, Martyna; Gabig-Cimińska, Magdalena; Moskot, Marta (Frontiers in Immunology, 2023)
Multiple biological processes in mammalian cells are implicated in psoriasis (Ps) development and progression, as well as in the pathogenic mechanisms associated with this chronic immune-mediated inflammatory disease (IMID). These refer to molecular cascades contributing to the pathological topical and systemic reactions in Ps, where local skin-resident cells derived from peripheral blood and skin-infiltrating cells originating from the circulatory system, in particular T lymphocytes (T cells), are key actors. The interplay between molecular components of T cell signalling transduction and their involvement in cellular cascades (i.e. throughout Ca2+/CaN/NFAT, MAPK/JNK, PI3K/Akt/mTOR, JAK/STAT pathways) has been of concern in the last few years; this is still less characterised than expected, even though some evidence has accumulated to date identifying them as potential objects in the management of Ps. Innovative therapeutic strategies for the use of compounds such as synthetic Small Molecule Drugs (SMDs) and their various combinations proved to be promising tools for the treatment of Ps via incomplete blocking, also known as modulation of disease-associated molecular tracks. Despite recent drug development having mainly centred on biological therapies for Ps, yet displaying serious limitations, SMDs acting on specific pathway factor isoforms or single effectors within T cell, could represent a valid innovation in real-world treatment patterns in patients with Ps. Of note, due to the intricate crosstalk between intracellular pathways, the use of selective agents targeting proper tracks is, in our opinion, a challenge for modern science regarding the prevention of disease at its onset and also in the prediction of patient response to Ps treatment.